2017
DOI: 10.1007/s10126-017-9766-4
|View full text |Cite|
|
Sign up to set email alerts
|

Recovery of Previously Uncultured Bacterial Genera from Three Mediterranean Sponges

Abstract: Sponges often harbour a dense and diverse microbial community. Presently, a large discrepancy exists between the cultivable bacterial fraction from sponges and the community in its natural environment. Here, we aimed to acquire additional insights into cultivability of (previously uncultured) bacteria from three sponge species, namely Aplysina aerophoba, Corticium candelabrum and Petrosia ficiformis, by studying bacterial growth on five media in the form of 60 communities scraped from plates without antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(78 citation statements)
references
References 66 publications
4
59
0
Order By: Relevance
“…Defining cultivability as the number of taxa that could be cultured divided by the total number of taxa detected in the sponge tissue, we report here a recovery of 2% of the spongeassociated taxa by cultivation. This falls into the range of other sponge-microbe cultivation experiments (Sipkema et al, 2011;Lavy et al, 2014;Keren et al, 2015;Esteves et al, 2016;Versluis et al, 2017), which report a recovery rate of 0.1 to 14%. Even though different sponge species harbor speciesspecific and highly divergent microbiota, it has been shown that their cultivable fractions are comparable (Li et al, 2007;Hardoim et al, 2014) since rare generalists are proliferating under laboratory conditions.…”
Section: Most Cultivated Taxa Differ From Sponge-associated Bacteriasupporting
confidence: 53%
See 4 more Smart Citations
“…Defining cultivability as the number of taxa that could be cultured divided by the total number of taxa detected in the sponge tissue, we report here a recovery of 2% of the spongeassociated taxa by cultivation. This falls into the range of other sponge-microbe cultivation experiments (Sipkema et al, 2011;Lavy et al, 2014;Keren et al, 2015;Esteves et al, 2016;Versluis et al, 2017), which report a recovery rate of 0.1 to 14%. Even though different sponge species harbor speciesspecific and highly divergent microbiota, it has been shown that their cultivable fractions are comparable (Li et al, 2007;Hardoim et al, 2014) since rare generalists are proliferating under laboratory conditions.…”
Section: Most Cultivated Taxa Differ From Sponge-associated Bacteriasupporting
confidence: 53%
“…Plates were divided in quadrants, and kanamycin disks (30 µg Thermo Fisher Scientific, Waltham, MA, United States, Oxoid Kanamycin Antimicrobial Susceptibility Disks) were placed in the approximate center of each of the quadrants, to prevent the growth of Pseudovibrio spp. in limited areas of the plates (Versluis et al, 2017). For each medium and its three dilutions, three replicate plate sets were used for incubation with (AP_positive) and without (AP_negative) aeroplysinin-1, and a negative control.…”
Section: (A) Platesmentioning
confidence: 99%
See 3 more Smart Citations